Implementasi Aplikasi Web Perbandingan Metode Saw dan Topsis dalam Pemilihan Supplier Terbaik - Saputri, Galuh; Sari, Willis Puspita; Suwarno, Joko (SENTRI: Jurnal Riset Ilmiah, 2025)
PT. PEB is one of the groups of PT. PBT which is engaged in industry. To support the raw material that is needed by the company, a decision support system is proposed in selecting the best supplier. This study aims to analyze supplier selection and can help provide analysis of suppliers based on the criteria desired by the company, there are 8 criteria, namely low prices, quality goods, timeliness in delivery, availability of goods, good service to customers, delivery time, discounts, and payment due. Then as an alternative, there are 50 suppliers who have collaborated with the company. The selection of the best suppliers was analyzed using the TOPSIS and SAW methods, the results obtained from each method. In the TOPSIS method, CV.AP got the highest score of 0.779 while the SAW method, CV.CH got the highest score of 0.963. Then the results of the calculation program speed of the two methods are also different, the TOPSIS method is completed in 0.0327 seconds and SAW is completed in 0.0371 seconds.